AB0577 TOCILIZUMAB IN GIANT CELL ARTERITIS. ROUTE OF ADMINISTRACION: INTRAVENOUS OR SUBCUTANEOUS. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: Recently, based on the GiACTA trial results, weekly subcutaneous Tocilizumab (TCZ) has been approved for the treatment of Giant Cell Arteritis (GCA). It has showed to be effective and safety. Objectives: Our aim was to compare the efficacy of TCZ according the route of administration. Methods: Multicenter study of 134 GCA patients in treatment with TCZ. It was performed a comparative study between 2 groups according the route of administration of TCZ, intravenous (IV) or subcutaneous (SC). Results: We study 134 patients divided in 2 groups: a) IV TCZ, 104 cases and, b) SC TCZ, 30 cases, with a mean age 73.4±8.2 years vs 71.9±10.6 years, respectively (p=0.501). Disease duration, clinical manifestations and acute phase reactants at TCZ onset were similar in both groups with non-statistical difference. 91.7% patients who received SC TCZ achieved prolonged remission after 12 months of treatment (p=0.043). And the glucocorticoid sparing effect of TCZ was greater in the same group, reaching a statistical difference at 3 and 24 months (p=0.017 and p=0.021). Patients under IV TCZ treatment suffered more adverse event during follow up (p=0.043). TABLE 1 and 2 summarizes the comparative study. Conclusion: Patients in treatment with SC TCZ, reached prolonged remission after 12 months of treatment and were able to discontinue prednisone dose after 24 months of follow up. The incidence of adverse events was more frequent in the IV TCZ group, without difference in relation to infections. References: [1] Stone JH, Tuckwell K, Dimonaco S, Klearman M, Aringer M, Blockmans D, et al. Trial of Tocilizumab in Giant-Cell Arteritis. N Engl J Med. 2017; 377:317-28. [2] Calderón-Goercke M. Tocilizumab in giant cell arteritis. Observational, open-label multicenter study of 134 patients in clinical practice. Semin Arthritis Rheum. 2019 Jan 5. pii: S0049-0172(18)30571-7. doi: 10.1016/j.semarthrit.2019.01.003. [Epub ahead of print] Disclosure of Interests: Monica Calderón-Goercke: None declared, J. Loricera: None declared, D. Prieto-Peña: None declared, Vicente Aldasoro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Ignacio Villa-Blanco: None declared, Alicia Humbría: None declared, Clara Moriano: None declared, Susana Romero-Yuste: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Elena Becerra-Fernández: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Carles Galisteo: None declared, Francisca Sivera: None declared, Alejandro Olive: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Carlos Fernández-López: None declared, Francisco Navarro: None declared, Enrique Raya: None declared, Eva Galindez: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Arantxa Conesa: None declared, Cristina Hidalgo: None declared, Carlos Vázquez: None declared, Jose Andrés Román-Ivorra: None declared, Pau Lluch: None declared, Sara Manrique Arija Speakers bureau: ABBvie, MSD, Janssen, Lillly, Roche, Pfyzer, Novartis., Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Eugenio de Miguel: None declared, Carmen Torres-Martín: None declared, Juan Carlos Nieto: None declared, Carmen Ordas-Calvo: None declared, Eva Salgado-Pérez: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen Larena: None declared, Natalia Palmou-Fontana: None declared, Vanesa Calvo-Río: None declared, Carmen González-Vela: None declared, Alfonso Corrales: None declared, María Varela-García: None declared, Elena Aurrecoechea: None declared, Raquel Dos-Santos: None declared, Ángel García-Manzanares: None declared, Norberto Ortego: None declared, Sabela Fernández: None declared, Francisco Ortiz-Sanjuán: None declared, Montserrat Corteguera: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen